MOTIVASI TRAVELLER MENGAKSES INSTAGRAM @ayokelilingindonesia - Nurul Fadzar Sukarni (Jurnal Pustaka Komunikasi, 2018)
The presence of social media of was globalization with the increasingly sophisticated telecommunication technology as it now brings an impact to the dynamics development of the world of communication that is increasingly easy and quickly accessible by anyone through a new way. With the diversity of communicated media available, it does not prevent people from connecting with each other, even increasing the creativity to be able to use it to become an important need in the side of life. Utilization of social media is then able to bridge the realization of the desire to be achieved such as getting information about something you want to know more. Instagram social media is expanding rapidly, the same as social media lawyer that has been there first. Instagram a lot of popular from various circles, both adults, teenagers, children with background work and education that when using it has a different motivation.